(untitled) (Journal of history-rus, 2024)
The article examines the life of Ahiko Tetsuro, a soldier of the Imperial Japanese Army, arrested in Kazakhstan as a result of World War II and remaining in Kazakhstan after his release, the conditions of his arrest, the nature of life in Kazakhstan. The camp is considered from the inside, from the point of view of Ahiko Tetsuro. In addition, the memoirs and interviews of Ahiko Tetsuro are a valuable source of information about the internment conditions in the Spassky camp, the fates of other Japanese, daily life in the camp, the level of equipment. Highlighting the life and experiences of Ahiko Tetsuro, the quality of life of prisoners accepted for free work in the Spassky camp, the daily routine in the camp, provision of necessary things, the amount of food, the nature of forced labor, and other aspects of camp life emerged anew. Not only about the situation in the Spassky camp, but also about the return of prisoners of war, especially Japanese, the consequences of the arrest, how Ahiko Tetsuro was captured and how his life continued after his release. Information about the historical period under consideration was obtained from the memoirs of Ahiko Tetsuro using methods of everyday research and historical hermeneutics. Keywords: Ahiko Tetsuro, World War II, Japanese prisoners of war, prisoners of war, prisoner of war camps, GULAG, Karlag, forced labor.